Variability and correlations among traits in soybean crosses (Scientia Agricola, 2002)
The estimation of parameters in initial inbreeding generations is important to direct the breeding program, mainly for the selection of the most promising genotypes. This research evaluated twenty-one soybean genotypes (six parents and their 15 diallel crosses in F2), in two locations (ESALQ and Anhembi) of Piracicaba, SP, Brazil. A randomized complete block design was adopted, with six replications in each location. The experimental plots were represented by 12 hills of individual plants spaced 0.80 m x 0.80 m. The evaluated traits were: number of days and plant height at flowering and maturity; agronomic value; seed yield; seed oil content; and oil yield. All parameter estimates were based on the components of the variance and covariance from individual and combined analyses. Parents and F2 presented variability for all the traits. In terms of favorable environmental quality, the two locations were good for the expression of the genetic potential of the genotypes, however Anhembi was the most favorable for the expression of seed yield. The genotype x location interaction was an important component of the phenotypic variation, except for seed oil content. The genotypic correlations were usually larger than the phenotypic and environmental, for the two locations. The magnitude of the phenotypic and genotypic correlations, showed that the phenotypes reflected the genotypes satisfactory. The traits related to flowering and to maturity were important for the improvement of seed yield, with prominence for agronomic value. There was an evidence of difficulties to develop new soybean genotypes with high seed yield and earliness.